The Effectiveness Of Weblog-Assisted Reading Module On Tertiary Engineering EFL Students’ Reading Comprehension In Pakistan - Khatoon, Sahib (2022)
This study aimed to design and develop the weblog-assisted reading module. Moreover, the study investigated the effectiveness of the weblog-assisted reading module on engineering students’ reading comprehension performance in terms of making predictions, finding out lexical information, analysing the main idea, and the summarisation strategies at the engineering university of Sindh, Jamshoro, Pakistan.